Integrating Artificial Intelligence into Shariah Islamic Banking Recommendations for The Development of Islamic Banking - Khoso, Prof. Dr. Aijaz Ali; Pathan, Dr. Muhammad Shoaib Khan (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
This article is based on the readiness of Islamic banking partners for in-depth discussion in the Shariah Commission. This is necessary to maintain knowledge of Islamic banking and finance, as well as to comply with Sharia law. This article discusses the inclusion of robo-advisors in the Shariah Committee on Sharia Law in real time. Demonstrate the capabilities of the Block Lock Management System (BMS) to strengthen Sharia compliance and auditing functions to ensure Sharia compliance for Islamic banks.